Expression of angiotensin II and its receptors in cyclosporine‐induced gingival overgrowth. (28th October 2012) - Subramani, T.; Senthilkumar, K.; Periasamy, S.; Rao, S.
<x xml:space="preserve">Abstract</x> Background and Objectives The renin–angiotensin system (RAS) is considered as a hormonal circulatory system involved in maintaining blood pressure, electrolyte and fluid homeostasis. RAS components can be synthesized in local tissues and are found to play a role in gingival overgrowth. The drug‐induced gingival overgrowth (DIGO) is a fibrotic condition, which is associated with multiple factors, including inflammation and adverse drug effects such as cyclosporine A. This study was directed forward to the identification of the angiotensinogen, angiotensin II (Ang II) and its receptors AT1/AT2 expression in DIGO tissues and cyclosporine‐treated human gingival fibroblast cells. Material and Methods Gingival samples were obtained from patients with cyclosporine‐induced gingival overgrowth, chronic periodontitis and normal healthy subjects. The total RNA was isolated and reverse transcription–polymerase chain reaction was performed for angiotensinogen, Ang II and AT1/AT2 receptor. Ang II protein was estimated from tissue by enzyme immunoassay. The expression of Ang II and its receptors were also examined in gingival fibroblast cells treated with cyclosporine. Results Ang II mRNA and protein expression was significantly higher in patients with DIGO than in patients with periodontitis and healthy subjects. The AT1 mRNA was expressed more than AT2 in all examined tissues. In gingival fibroblasts, Ang II and AT1 expressions were increased with cyclosporine incorporation compared to controls. Conclusion These results suggest that cyclosporine can modulate local expression of RAS components such as angiotensinogen, Ang II and its receptors in gingival tissues and gingival fibroblast cells.